Peran Hadist Ahkam dalam Mewujudkan Syarat Wali Nikah dan Kedudukanya Menurut Pandangan Madhab Syafi’iyah - Nur Muhammad Saifurrijal; Muhammad Rizal Afandi; Zikrullah Yanderi (CV. Lentera Literasi Indonesia, 2025)
Marriage is a bond that is built by two men and women to continue the offspring of the two people. The impact of the marriage is that a new family will be born. do not forget that a very important thing in marriage is to fulfill the terms and conditions according to the applicable Islamic law. In the discussion of this article, researchers used the library research method (library research) which was carried out from the shafi'iyah madhhab. From the many requirements and pillars in marriage, researchers narrowed down the discussion to the requirements and position of the marriage guardian according to the views of the shafi'iyah madhhab, because without a guardian in marriage, the marriage will not be valid, therefore the existence of a guardian is very important in a marriage.